Mas‐related G protein‐coupled receptor type D antagonism improves portal hypertension in cirrhotic rats. Issue 9 (20th May 2022) - Gunarathne, Lakmie S.; Rajapaksha, Indu G.; Casey, Stephen; Qaradakhi, Tawar; Zulli, Anthony; Rajapaksha, Harinda; Trebicka, Jonel; Angus, Peter W.; Herath, Chandana B.
Abstract: Splanchnic vasodilatation contributes to the development and aggravation of portal hypertension (PHT). We previously demonstrated that in cirrhosis, angiotensin‐ mediates splanchnic vasodilatation through the Mas receptor (MasR). In this study, we investigated whether the recently characterized second receptor for angiotensin‐(1–7), Mas‐related G protein‐coupled receptor type D (MrgD), contributes to splanchnic vasodilatation in cirrhotic and noncirrhotic PHT. Splanchnic vascular hemodynamic and portal pressure were determined in two rat models of cirrhotic PHT and a rat model with noncirrhotic PHT, treated with either MrgD blocker D‐Pro 7 ‐Ang‐(1‐7) (D‐Pro) or MasR blocker A779. Gene and protein expression of MrgD and MasR were measured in splanchnic vessels and livers of cirrhotic and healthy rats and in patients with cirrhosis and healthy subjects. Mesenteric resistance vessels isolated from cirrhotic rats were used in myographs to study their vasodilatory properties. MrgD was up‐regulated in cirrhotic splanchnic vessels but not in the liver. In cirrhotic rats, treatment with D‐Pro but not A779 completely restored splanchnic vascular resistance to a healthy level, resulting in a 33% reduction in portal pressure. Mesenteric vessels pretreated with D‐Pro but not with A779 failed to relax in response to acetylcholine. There was no splanchnic vascular MrgD or MasR up‐regulation in noncirrhotic PHT; thus, receptor blockers had no effect on splanchnic hemodynamics. Conclusion : MrgD plays a major role in the development of cirrhotic PHT and is a promising target for the development of novel therapies to treat PHT in cirrhosis. Moreover, neither MrgD nor MasR contributes to noncirrhotic PHT. Abstract : Blockade of the Mas Related G Protein‐coupled receptor type‐D (MrgD) produced a large increase in splanchnic resistance and a marked reduction in portal pressure in cirrhotic rats. Interestingly, the upregulation of MrgD was confined to cirrhotic splanchnic vessels thus drugs that inhibit MrgD may reduce splanchnic vasodilation without adversely affecting the hepatic resistance. Therefore, MrgD is a promising target for the design and development of novel splanchnic vasculature‐specific therapies to treat portal hypertension in cirrhosis. image